The preoperative SOFA score and remnant small intestine length are postoperative risk factors for mortality in patients with non‐occlusive mesenteric ischemia: a case–control study - Kazufumi Umemoto; Kentaro Kato; Takumi Yamabuki; Minoru Takada; Yoshiyasu Ambo; Fumitaka Nakamura; Satoshi Hirano (Acute Medicine & Surgery, 2023)
Aim Non‐occlusive mesenteric ischemia (NOMI) is a fatal condition with a low survival rate in most cases. The risk factors for perioperative mortality in NOMI cases are unclear. The purpose of this study was to define the risk factors for mortality in patients with NOMI undergoing surgery. Methods Thirty‐eight consecutive patients who underwent surgery for NOMI at Teine Keijinkai Hospital between 2012 and 2020 were included in the study. Patient information, including age, sex, physical findings, comorbidities, laboratory data, and computed tomography and surgical findings were retrospectively analyzed. Results Of the 38 patients, 18 (47%) died before discharge. Significant univariate predictors of mortality were a high Sequential Organ Failure Assessment (SOFA) score, high lactate level, low blood pH, and short intestinal length after surgery. In the multivariate analysis, a high SOFA score (odds ratio 1.33, P = 0.036) and short intestine length after surgery (odds ratio 34.7, P = 0.003) were identified as independent risk factors for perioperative mortality. Conclusion The preoperative SOFA score and postoperative residual intestinal length may be predictors of death in NOMI surgical patients, not age and the content of comorbidities.